Lipid profile and dyslipidemia among school-age children in urban Ghana - Anna Lartey; Grace S. Marquis; Richmond Aryeetey; Helena Nti (BMC, 2018)
Abstract Background Dyslipidemia during childhood has been associated with higher risk of atherosclerosis later in life. Information on the lipid profile of Ghanaian children is scarce. The aim of this study was to assess the lipid profiles of school children between the ages of 9-15 years, living in urban Ghana. Methods A total of 802 randomly selected school-age children participated in the Ghana School Survey implemented in Kumasi and Accra, Ghana. A structured questionnaire was used to collect information on child and maternal socio-demographic characteristics (including age, education, and occupation), 7-day food frequency, home and school activity, as well as measurement of weight and standing height. Weight, height, and age data were converted into BMI-for-age indices to determine weight status. Finger-prick fasting blood samples were taken from the school-age children. Total cholesterol (TC), triglyceride (TG), high density lipoprotein (HDL-C) and low-density lipoprotein (LDL-C) cholesterol levels were determined using the CardioChek® PA Test System. Reference lipid levels based on the US National Cholesterol Education Program 2001 guidelines were used to determine the proportion of children with dyslipidemia. Results The mean TC, LDL-C, HDL-C, and TG levels were 149.0 ± 57.0 mg/dl, 80.1 ± 38.6 mg/dl, 53.5 ± 19.4 mg/dl, and 71.4 ± 54.7 mg/dl, respectively. Mean TC/HDL-C ratio was 3.0 ± 1.0. The proportion of children with abnormal values were 12.1% for TC, 4.5% for TG, 28.4% for HDL-C, 9.2% for LDL-C, and 6.6% for TC/HDL-C ratio. The levels of dyslipidemia (HDL, LDL, and TC/HDL-C ratio) were higher among overweight/obese compared to normal-weight children. More frequent fruit consumption was also linked with lower LDL-C (p = 0.020) while watching television (TV) in the mornings was linked with both higher TC (p = 0.011) and TG (p = 0.006). Conclusions Majority of urban-dwelling Ghanaian school children had normal lipid profiles. However, the higher levels of dyslipidemia observed among overweight and obese children suggest the need for population level physical activity and dietary interventions among children to reduce risk of cardiovascular diseases in adult life.